End-of-life care in children and adolescents with cancer: perspectives from a French pediatric oncology care network. Issue 3 (June 2022) - Blais, Sophie; Cohen-Gogo, Sarah; Gouache, Elodie; Guerrini-Rousseau, Lea; Brethon, Benoit; Rahal, Ilhem; Petit, Arnaud; Raimondo, Graziella; Pellegrino, Beatrice; Orbach, Daniel
Background: In developed countries, cancer remains the leading cause of pediatric death from illness after the neonatal period. Objective: To describe the end-of-life care characteristics of children and adolescents with solid tumors (ST) or hematologic malignancies (HM) who died from tumor progression in the Île-de-France area. Methods: This is a regional, multicentric, retrospective review of medical files of all children and adolescents with cancer who died over a 1-year period. Extensive data from the last 3 months of life were collected. Results: A total of 99 eligible patients died at a median age of 9.8 years (range, 0.3–24 years). The most frequent terminal symptoms were pain (n = 86), fatigue (n = 84), dyspnea (n = 49), and anorexia (n = 41). Median number of medications per patient was 8 (range, 3–18). Patients required administration of opioids (n = 91), oxygen (n = 36), and/or sedation (n = 61). Decision for palliative care was present in all medical records and do-not-resuscitate orders in 90/99 cases. Symptom prevalence was comparable between children and adolescents with ST and HM. A wish regarding the place of death had been expressed for 64 patients and could be respected in 42 cases. Death occurred in hospital for 75 patients. Conclusions: This study represents a large and informative cohort illustrating current pediatric palliative care approaches in pediatric oncology. End-of-life remains an active period of care requiring coordination of multiple care teams.